Phosphate rock utilization by soybean genotypes on a low-P savanna soil and the status of soil P fractions after a subsequent maize crop - Nwoke, O.C.; Okogun, J.A.; Sanginga, Nteranya; Diels, J.; Abaidoo, Robert C.; Osonubi, O. (2009)
Information on the inter- and intra-specific variability in the acquisition and utilization of phosphorus (P) by promiscuous soybean genotypes under low-P conditions can be helpful in the short-term management of soil P availability. Thirteen promiscuous soybean genotypes were evaluated in a low-P soil at Fashola in the derived savanna of Nigeria to compare their ability to acquire and utilize P from phosphate rock (PR) and single superphosphate (SSP). Changes in soil P fractions after a subsequent maize crop were also assessed. The treatments were 90 kg P/ha added as PR (90-PR), 30 kg P/ha as SSP (30-SSP), and 0 kg P/ha as a control (0-P). Large differences occurred in growth, nodulation, and mycorrhizal infection rates among the soybean genotypes and were related to the P sources. Three genotypes (Tgm 1511, Tgm 1419, and Tgm 1360) increased their shoot dry matter yield significantly with PR application. The efficiency of the genotypes to acquire and utilize fertilizer or soil P differed significantly, and their ranking depended on how efficiency is defined. Shortly after application, 90-PR and 30-SSP resulted in similar increases in available P but the effects of 90-PR on the Ca-bound pool were significantly higher than those of 30-SSP. The difference in Ca-bound P between 90-PR and 0-P decreased from 44 to 26 mg/kg after the second cropping, leading to significantly higher levels of resin- P (p = 0.006) and HCO 3-Pi (p = 0.038) in the PR treatment than in the control. The results of this study indicate that exploiting genotypic differences in P use efficiency may lead to the selection of soybean genotypes that can potentially enhance productivity in the low-P savanna soils.